ASSESSMENT OF PHENOTYPIC DIVERSITY OF BISKRA DATE PALM (PHOENIX DACTYLIFERA L.) CULTIVARS - BEDJAOUI, HANANE; BENBOUZA, HALIMA (Courrier du Savoir; No 26 (2018): Courrier du Savoir, 2018)
Date palm is an important fruit crop for Algeria due to its economic importance. More date palm is considered as a staple food for many regions in Algeria. Biskra is the first biggest region for dates production, mainly for the commercial cultivar Deglet Noor.  The present study aimed at phenotypic diversity charaterization among fifteen Algerian date palm cultivars grown in Biskra using fifteen descriptors measured on vegetative part. The results, using multivariate analysis, indicated high morphological variability among cultivars. Globally, correlation matrix showed relatively high positive and negative correlations between some vegetative characters.  Principal component analysis (PCA) defined the most discriminants characters responsible of the observed variability. In fact, among the fifteen vegetative traits analyzed in this study, five related to the different descriptors of the leaf, leaflet and spines allowed effective differentiation among the studied cultivars. The data obtained here constitute a contribution to help to create a phenotypic database and also to highlight the importance of neglected cultivars.